Analysis of the Influence of MyTelkomsel App as a Digital Touch Point on Digital Business Performance at PT. Telkom Indonesia - Junaedi Junaedi; Tasya Millenia (Publikasi Indonesia, 2024)
In the digital era, digital transformation is a must for companies to compete. PT. Telkom Indonesia introduces the MyTelkomsel app as a digital touch point. This study aims to analyze the influence of the MyTelkomsel application on Telkom's digital business performance. The research method used is quantitative descriptive with a literature study approach. The research data was collected from two main sources, namely literature studies and analysis of the company's financial statements. The results of the study show that the MyTelkomsel application has a positive influence on Telkom's digital business performance. This is evidenced by the increase in the number of MyTelkomsel App users, customer satisfaction, and company revenue.